ChemInform Abstract: All‐Metal Antiaromaticity in Sb4‐Type Lanthanocene Anions. Issue 27 (16th June 2016) - Min, Xue; Popov, Ivan A.; Pan, Fu‐Xing; Li, Lei‐Jiao; Matito, Eduard; Sun, Zhong‐Ming; Wang, Lai‐Sheng; Boldyrev, Alexander I.
Abstract: Compounds (IIIa—e) crystallize in the triclinic space group P1 with Z = 2 (single crystal XRD).